Improving students’ speaking skills with the Numbered Heads Together technique - Verawaty Verawaty (Universitas Syiah Kuala, 2016)
This research was done to find out whether the Numbered Heads Together (NHT) technique can improve students’ speaking skills, and find out the students’ responses toward the implementation of the NHT technique for teaching speaking. This research was a Classroom Action Research (CAR) study and was done in 2 cycles with year 11 students at SMA 1 Darul Imarah at Lampeuneurut in Aceh Besar. The procedure of the research consisted of planning the actions, implementing the actions, observing the actions, and reflections. The instruments used in collecting the data were tests, observation sheets for the researcher and the students and a questionnaire. The results from the research showed that the NHT technique gave better results in improving the students’ speaking skills, in sharing information and in delivering ideas. This can be seen in the results from the tests, where the mean score was 60 before the actions which increased to 67 at the end of cycle 1 and to 82 at the end of cycle 2. Furthermore, the percentage of students’ participation in the teaching-learning processes increases significantly. This was shown by the results from the observation sheets where the percentage of the students’ involved was 67% (criteria of enough) in the first cycle and increased to 98% (criteria = very good) in the second cycle. This meant that the students then worked well in running all of the activities. Furthermore, based on the result from the questionnaire, the mean score obtained by the students was 3.01 (agree). This showed that the students responded positively toward the implementation of the NHT technique. Thus, it is suggested that teachers who have problems in teaching speaking try to implement the NHT technique.